Auto light saving system with counter / Amirul Azri Mohd Yusof and Muhammad Syahril Hussin - Mohd Yusof, Amirul Azri; Hussin, Muhammad Syahril (2015)
Automatic light saving system is a reliable circuit that takes over the task of controlling the room lights as well as counting number of persons visitors in the room very accurately. When somebody enters into the room then the counter is incremented by one and the light in the room will be switched ON and when any one leaves the room then the counter is decremented by one. The light will be only switched OFF until all the persons in the room go out. The total number of persons inside the room is displayed on the seven segment displays. The microcontroller does the above job. It receives the signals from the sensors, and this signal is operated under the control of software which is stored in ROM. Microcontroller AT89S52 continuously monitor the Infrared Receivers. When any object pass through the IR Receiver's then the IR Rays falling on the receivers are blocked. This obstruction is sensed by the Microcontroller.